Жизнь, искания, встречи. - Чаклин В.Д.; Chaklin V.D. (My University, 2000)
Остання з 13 книг видатного хірурга ортопеда-травматолога XX століття Василя Дмитровича Чакліна, написана ним незадовго до смерті (1976 р.), не є автобіографією. Вона відображає великий життєвий досвід автора, починаючи зі студентських років до похилого віку, 55-річний шлях наукових пошуків і переживання лікаря, вченого, великого організатора науки і лікувального процесу. У книзі відображені творчі періоди організації наукових центрів на Уралі та в Москві, створення в кожному з них шкіл активних хірургів ортопедів-травматологів та систем надання допомоги пацієнтам із пошкодженнями та захворюваннями опорно-рухової системи у великих регіонах країни. Приділяється увага боротьбі думок у галузі хірургії та ортопедії-травматології. Також описується велике відкриття автора — оперативне втручання на тілах хребців і міжхребцевих дисках (1931 р.), яке започаткувало сучасну хірургію хребта і створення нового розділу науки — вертебрології.

The last of 13 books by the outstanding surgeon and orthopedic traumatologist of the 20th century, Vasily Dmitrovich Chaklin, written by him shortly before his death (1976), is not an autobiography. It reflects the author's extensive life experience, starting from his student years to old age, a 55-year journey of scientific research and experiences of a doctor, scientist, a great organizer of science and the medical process. The book reflects the creative periods of the organization of scientific centers in the Urals and in Moscow, the creation in each of them of schools of active surgeons orthopedic traumatologists and systems of providing assistance to patients with injuries and diseases of the musculoskeletal system in large regions of the country. Attention is paid to the struggle of opinions in the field of surgery and orthopedic traumatology. The author's great discovery is also described - surgical intervention on the vertebral bodies and intervertebral discs (1931), which initiated modern spinal surgery and the creation of a new branch of science - vertebrology.
Life, searching, meetings.